Pengaruh Variasi Tebal Sudu Terhadap Kinerja Kincir Air Tipe Sudu Datar - Wahyudi, Slamet; Cahyadi, Dhimas Nur; Purnami, Purnami (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2012)
Waterwheel is a means to change the water energy into mechanical energy in the form of torque on the wheel shaft. Working waterwheel by the large flow and high utilization of water falls. Today the water wheel still has a small efficiency when compared to water turbines that exist at the moment. Therefore, it still needs further research to improve the efficiency of the water wheel. The purpose of the study is to determine the performance of the blade thickness variation waterwheel flat blade type. In this study, using a kind of overshot waterwheel with a thickness variation of different blades of 0.3; 0.6; 0.9; and 1.2 cm and a water capacity of 10-20 m3/hr. Furthermore be obtained shaft power and efficiency of the water wheel. By using statistical analysis showed that the shaft power and efficiency is influenced by variations in thick blade. In this test shaft power and highest efficiency artifacts on blade 0.3 cm thick.Keywords: windmill water, the thickness of the blade, the performance